1997
DOI: 10.1086/304860
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Optical Flux Limits from Gamma‐Ray Bursts Measured by the Gamma‐Ray Optical Counterpart Search Experiment

Abstract: The Gamma-Ray Optical Counterpart Search Experiment (GROCSE) presents new experimental upper limits on the optical flux from gamma-ray bursts (GRBs). Our experiment consisted of a fully-automated very wide-field opto-electronic detection system that imaged locations of GRBs within a few seconds of receiving trigger signals provided by BATSE's real-time burst coordinate distribution network (BACODINE). The experiment acquired 3800 observing hours, recording 22 gamma-ray burst triggers within ∼30 s of the sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…After many years of unsuccessful attempts to catch the optical signal of a γ -ray burst in progress (see e.g. McNamara et al 1995, Krimm et al 1996, Hudec & Soldan 1995, Lee et al 1997, Park et al 1997, the first such simultaneous detection was made of GRB 990123 by Akerlof et al (1999). The robotic camera ROTSE, triggered by BATSE, started a sequence of optical Figure 16 The R light curve of GRB 980326, with model curves representing the power-law decay of a relativistic afterglow superposed with the light curve of SN 1998bw, shifted to various redshifts .…”
Section: Prompt Optical Emissionmentioning
confidence: 99%
“…After many years of unsuccessful attempts to catch the optical signal of a γ -ray burst in progress (see e.g. McNamara et al 1995, Krimm et al 1996, Hudec & Soldan 1995, Lee et al 1997, Park et al 1997, the first such simultaneous detection was made of GRB 990123 by Akerlof et al (1999). The robotic camera ROTSE, triggered by BATSE, started a sequence of optical Figure 16 The R light curve of GRB 980326, with model curves representing the power-law decay of a relativistic afterglow superposed with the light curve of SN 1998bw, shifted to various redshifts .…”
Section: Prompt Optical Emissionmentioning
confidence: 99%
“…Rapid follow-up observations in the optical are critical to understand the physical processes of GRBs. There are quite a few small robotic telescopes, in addition to ROTSE-III, that have been built and installed around the world in order to rapidly search for GRB optical counterparts, e.g., GROCSE (Park et al 1997), TAROT (Klotz et al 2009), SkyNet 4 , WIDGET (Urata et al 2011), MASTER 5 , Pi of the Sky (Burd et al 2005), RAPTOR (Vestrand et al 2002), REM (Zerbi & Rem Team 2001), and Watcher GRBs.…”
Section: Discussionmentioning
confidence: 99%
“…Although this discovery marks another milestone in comprehending the physics of GRBs, bright optical tran-sients (OTs) may be the exception rather than the rule. Both LOTIS and ROTSE have unsuccessfully attempted to detect these predicted flashes on many occasions [3][4][5][6][7][8]. Although some of the non-detections may be attributed to large extinction, GRB 990123 demonstrated that the progenitor is not always obscured.…”
Section: Introductionmentioning
confidence: 99%